MORPHOMETRIC PARAMETERS OF THE SPLEEN IN THE EARLY ANTENATAL PERIOD OF DEVELOPMENT - Zayniddinov Ogʻabek Farxod oʻgʻli,; Oʻrazdurdiyeva Muqaddas,; Egamberganova Mohimjon Mahmudjon qizi,; Ikromova Shahlo Anvarovna Pediatrics, Group 204,; Muxammadjonov Lochinbek, (TADQIQOTLAR, 2026)
Abstract. In the study of spleen specimens from embryos and fetuses, at the 5th–6th week a primary splenic rudiment was identified within the dorsal mesogastrium. By weeks 8–9, distinct red and white pulp precursors became recognizable, with early lymphocyte populations appearing in the periarteriolar sheaths. By weeks 11–12, the spleen demonstrated well-formed trabecular framework, sinusoidal vasculature, and primary  lymphoid  follicles.  Two  peaks  of  active  lymphocyte  proliferation  were established: at 18–20 weeks and at 27–28 weeks of embryogenesis, coinciding with intensification  of  extramedullary  hematopoiesis  and  expansion  of  the  white  pulp compartment.